Implementas Mesin Pengering “Cabinet Dryer” pada UMKM “RISQI” Desa Curah Cottok, Kapongan, Situbondo, Jawa Timur - andrew joewono; Adriana Anteng Anggorowati; Dyna Rachmawati; Lorensius Anang Setiyo Waloyo (Seminar Nasional Penelitian dan Abdimas, 2023)
The onion crackers produced by Mrs. Tutik are a micro-scale business in the cracker industry. This business has been established since 2016, Mrs. Tutik is an entrepreneur who has a desire to advance her business. However, they have not used more advanced (manual) production equipment (machines). Until now, Mrs. Tutik's crackers are only sold in the vicinity of the village, and village markets which are in the same area as Kapongan District.The food consumption pattern of the East Java population cannot be separated from crackers, which creates a large market opportunity for the "RISQI" MSME business. Data on the consumption of crackers by the Indonesian population in 2019 reached 200 tons per day. 25% of the consumption is supplied by large cracker companies, the difference is supplied by small and medium enterprises. Therefore, the business potential of "RISQI Crackers" (Tutik's mother) to develop is quite large.The potential and efforts to realize Mrs. Tutik's Kerupuk business in increasing her business capacity are carried out with mentoring activities starting from the stages of improving the production system and using production equipment that meets processed food production standards and business management system assistance. The assistance that will be carried out, namely: (1) increasing production capacity using an energy-efficient cracker drying machine, from 25 kg for each production, after the activity develops to 50 kg for one production, (3) assistance for preparing a simple cost analysis, (4) assistance to monitor sales activitiesCommunity service activities in the form of assistance to UMKM "RISQI" is an ongoing effort from the community development program that has been agreed in the MOU together with the village government of Curah Cottok, and is a downstream research result, the results of this Community Service are expected to provide outcomes in the form of increased production results from effectiveness production time, with the output of public service results.